Stakeholder theory: A qualitative, cross-sectional study describing customer perceptions of Fast Moving Consumer Goods (FMCG) companies’ sustainability involvement in minimising plastic pollution in Durban, KwaZulu-Natal - Thom, Elizabeth (The IIE, 2018)
Studies from the World Wide Fund (2018) illustrate that only 16% of plastic waste is recycled in South Africa. According to research, globally eight million metric tons, a year of plastic waste ends up in the ocean from careless mismanaged waste. The Fast Moving Consumer Goods (FMCG) industry is said to be one of the largest contributors to the production of plastic (WWF, 2018). A growing awareness from society surrounding the detrimental effects plastic has on the environment is putting immense pressure on companies to implement the necessary strategies to curb the problem (Fourie, 2014). For CSR initiatives to help build positive relationships between companies and their stakeholders, effective CSR communication is indispensable. Therefore, understanding customer perceptions of FMCG companies’ sustainability involvement could encourage companies to become more involved within the community to solve the problem. A qualitative, in-depth interview questionnaire was utilised to gather the information from seven random individuals, providing the researcher with an in-depth understanding of the perceptions, experiences and attitudes of customers on FMCGs’ plastic pollution involvements. Findings suggest that customers perceive FMCGs to be unsustainable as customers demonstrated they were unaware of any marketing strategies made by FMCGs on their involvement. Affordability and convenience are motivating factors for consumers during the decision-making process of sustainability.
Keywords: consumer decision making; Fast Moving Consumer Goods (FMCG); plastic pollution; Corporate Social Responsibility (CSR); sustainability